PEMANFAATAN ARTIFICIAL INTELLIGENCE DALAM BIDANG KESEHATAN - Ganis Sanhaji; Amirul Irsyaad Hizbullah (STKIP PGRI Situbondo, 2024)
The existence of Artificial Intelligence (AI) technology has changed the landscape in every field, especially in the health sector, optimizing medical data analysis, making diagnoses, and personalizing treatment. This article explores the application of AI in healthcare, highlighting its potential to improve patient outcomes, improve medical decision-making, and optimize healthcare delivery. This article also explores the ethical challenges and considerations associated with the integration of AI in healthcare. The article concludes by looking into the future of AI in healthcare, emphasizing the importance of collaboration between healthcare professionals and AI systems to optimize its potential